Criação e apropriação de valor: estudo de caso na indústria de software - Carvalho, Samuel de Souza (2018)
This dissertation aims to provide a better understanding of the dynamics of value creation and appropriation, by testing the applicability of the model derived from the notion of economic value (BRANDENBURGER; STUART, 1996) in the software market, taking into account the economic phenomena that are particular to this industry. Those phenomena, such as the network effects, switching costs, lock-in and similars were uncommon in the industrial economy, according to Varian (2003) and are the norm in the information economy. The research strategy adopted was the single case study with qualitative research, which had as data collection techniques a series of in-depth interviews applied to managers of the company with a semi-structured script and documentary analysis. The company studied has a representative role in the national software industry and presence in other Latin American countries, with a focus on providing business management systems for the retail segment. At the end of the study, it was verified that the creation and capture of value in the software sector needs to consider the rapid technological evolution that permeates the sector, not forgetting what Shapiro and Varian (1998a) argue that despite the fact that the economy has changed and is now ruled in information, how market laws continue as their own. The results indicated that both the product development and go to market strategies and the competitive dynamics of the markets in which the company operates affect its ability to create value and to appropriate value. Some economic effects such as the network effect and lock-in contribute for the company to maintain good margins, especially when its market share is high. In some cases, it has been observed that the network and system effects may be more decisive for the migration from one supplier to another than the lockin effect, considering the switching costs. In general, these phenomena vary in intensity in order to benefit or harm the company according to the strategies adopted for the positioning of the products.